Effects of Hypertension, Diabetes Mellitus, and Gender on Post Stroke Cognitive Impairment: Meta-Analysis - Sukandriani Utami; Emirza Nur Wicaksono; Amalia Choirunnisa; Nindita Arum Veibiani; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: Post-stroke cognitive impairment is a serious problem that is often faced by indivi-duals who have experienced a stroke. This study aims to determine and estimate the effects of hypertension, diabetes mellitus, and gender on post-stroke cognitive impairment through meta-analysis of primary research conducted by previous researchers.Subjects and Method: This was a meta-analysis study using the PICO model which includes; P: post-stroke patients. I: hypertension, diabetes mellitus, and women. C: normotensive, without diabetes mellitus, and men. O: post-stroke cognitive impairment. A systematic search for primary studies was carried out in the PubMed database which was published from 2014 to 2023. The keywords used to search for primary studies were "Hypertension" AND "Diabetes Mellitus" AND "Post Stroke Cognitive Impairment". The inclusion criteria for the articles searched were primary studies with cross-sectional and cohort studies from 2014-2023 and reporting aOR values. Primary studies were selected using the PRISMA diagram and relevant primary studies were analyzed using Review Manager 5.3.Results: There were 18 primary studies with cross-sectional and cohort study designs. The total sample obtained through a systematic review and meta-analysis was 9,103 post-stroke patients from France, China, Singapore, the Netherlands, Egypt, Ethiopia, and Uganda. The results of the analysis showed that hypertension increased the risk 1.56 times (aOR= 1.56; 95% CI= 1.11 to 2.19; p= 0.010) and diabetes mellitus increased the risk 1.58 times (aOR= 1.58; 95% CI= 1.23 to 2.05; p< 0.001) post-stroke cognitive impairment compared to people without hypertension and diabetes. Meanwhile, the female gender increases the risk of post-stroke cognitive impairment by 1.28 times (aOR= 1.28; 95% CI=1.16 to 1.42; p<0.001). The data is statistically significant.Conclusion: hypertension, diabetes mellitus, and female gender increase the risk of post-stroke cognitive impairment. Keywords: Hypertension, diabetes mellitus, women, post-stroke cognitive disorders